Desempenho acadêmico: uma explicação pautada nos valores humanos, atitudes e engajamento escolar - Sousa, Deliane Macedo Farias de (2013)
This thesis aimed to know in what extent values, attitudes toward schooling context and learning, and school engagement predict academic performance. Moreover, we intended to develop two psychological measures [Self-Evaluation of Academic Performance Scale (SEAAS) and Attitudes toward Schooling Context Scale (ASCS)], adapt the Attitudes toward Learning Scale (ATLS) to Brazilian context and verify their psychometric parameters. The Study 1 refers to elaboration process of measures and counted with 481 students from 6th to 9th grades of public and private schools from João Pessoa (PB), with average age of 12,9 years-old (sd = 1,59), equally distributed by sex. Participants answered a questionnaire with opened questions regarding academic performance and school context. The answers were examined by an automatic content analysis (ALCESTE) and items were formulated from them to compose both SEAAS and ASCS. The Study 2, presents the psychometric parameters of referred measures, and also of ATLS. Participated 200 students from High School, mostly females (53,5%), with average age of 12,6 years-old (sd = 1,50). The exploratory analysis of SEAAS, distinguished two components: satisfaction (α = 0,92, rm.i. = 0,39) and dissatisfaction with academic performance (α = 0,80, rm.i. = 0,25). Regarding the ASCS, were extracted three components from its items: attitudes toward teachers (α = 0,90, rm.i. = 0,45), school (α = 0,85, rm.i. = 0,43) and classmates (α = 0,85, rm.i.). Lastly, the original four-factor structure of ATLS were confirmed in this context: openness (α = 0,86, rm.i = 0,40), negative disposition (α = 0,77, rm.i = 0,40), expectative (α = 0,76, rm.i = 0,35) and anxiety (α = 0,73, rm.i = 0,31) related to learning. Since the measures reached suitable patterns of validity and precision, we performed the Study 3. With a sample of 210 students, basically with same characteristics of samples from previous studies, this study aimed to confirm the factorial structure of these three measures. The results showed that all of them presented satisfactory fit indexes, although they also have showed that for SEASS it is more adequate consider only one factor. In the Study 4, we looked for knowing in what extent academic performance is related to variables aforementioned. To reach this goal we counted with 200 students who answered to Basic Values Survey (BVS), School Engagement Scale (SES) and socio-demographic questions, besides the three measures from study 3. Academic performance was correlated with all variables considered, except with excitement values and expectations from learning. In this sense, we performed multiple linear regressions to know the predictive relations between these variables, resulting in an explanatory model of academic performance. The study 5, describes the testing of hierarchical model: values (normative, interactive and suprapersonal) → educational attitudes (toward school context and learning) → school engagement → academic performance. With a sample of 425 students from High School, this model has shown promising, with satisfactory fit indexes [²/gl = 1,99, GFI = 0,96, AGFI = 0,92, CFI = 0,94 e RMSEA = 0,07 (IC90% = 0,03-0,10)]. The goals of this thesis were reached, emphasizing the functional theory of human values. We hope that the results presented here might be useful to ground future researches and interventions to promote improvement in students’ academic performance.